Stress axis and osteopathy: A dual hormone approach. (September 2019) - Sampath, Kesava Kovanur; Katare, Rajesh; Tumilty, Steve
Abstract: Manual therapy initiates a cascade of neurophysiological changes in various systems including the peripheral nervous system, autonomic nervous system and the endocrine system. Of particular focus of this review was the hypothalamic-pituitary-adrenal (HPA) axis. When faced with a stressor, the HPA axis provides the frontline of defence resulting in the production of cortisol, measurement of which has been shown to be a reliable indicator of HPA axis activity. Manual therapy has been shown to influence the HPA axis. However, a functional cross-talk has been clearly demonstrated between the HPA axis and the hypothalamic-pituitary-gonadal (HPG) axis, with cortisol and testosterone inhibiting each other at all levels. This mutual inhibition may mean that multiple measures across these two systems (HPA-HPG axis) should be considered to provide an accurate representation of stress physiology. The balance between testosterone and cortisol represented as a ratio termed T/C ratio has been used for this purpose. Given the implicit role of the HPA-HPG axis in pain and inflammation and an apparent gender difference in pain perception and treatment response, T/C ratio may be of interest to osteopaths as it may enable us to capture the holistic effects of osteopathy. This review revisits the function of the HPA axis in pain and inflammation, presents a dual hormone approach in measuring the HPA axis and evaluates the implications for osteopathic practice and research. Highlights: HPA axis plays an important role in pain and/or inflammation. Manual Therapy may influence HPA axis activity. T/C ratio may provide a better estimation of HPA/stress axis response. Interaction between the HPA and HPG Axis must be considered in future studies.